2015
DOI: 10.1002/cctc.201500464
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Phosphine Ligands for the Methoxycarbonylation of Medium‐Chain Alkenes

Abstract: The methoxycarbonylation reaction provides ar oute to the synthesis of esters from medium-chain alkenes that may be used as fuel supplements. However,t he known productivec atalytic systems are expensive and/or unstablea te levated temperatures. Most of the data availableo nt he methoxycarbonylation of alkenes is derivedf rom ethylene and styrene as substrates. To broaden the scope, we conducted ac omparative study of ar ange of phosphine ligandsu nder comparable conditions fort he methoxycarbonylation of 1-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 98 publications
0
7
1
Order By: Relevance
“…Based on our earlier reports on the alkoxy‐ and the thiocarbonylation of alkenes at ambient temperature, a modified Pd 0 ‐based catalytic system for lactonization was identified . We found that the combination of [Pd(dba) 2 ], ligand L1 (dppdtbpf; 1‐diphenylphosphino‐1′‐(di‐ tert ‐butylphosphino)‐ferrocene) and diphenylphosphoric acid (DPPA) that was previously used in the thiocarbonylation led to 81 % of 2 a (Table , entry 1). Whereas, the original alkoxycarbonylation conditions ( L2 , (dtbpx; bis(di‐ tert ‐butylphosphinomethyl)benzene)/BNPA (1,1′‐bi‐2‐naphthol phosphoric acid)) generated only 73 % yield (entry 2).…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…Based on our earlier reports on the alkoxy‐ and the thiocarbonylation of alkenes at ambient temperature, a modified Pd 0 ‐based catalytic system for lactonization was identified . We found that the combination of [Pd(dba) 2 ], ligand L1 (dppdtbpf; 1‐diphenylphosphino‐1′‐(di‐ tert ‐butylphosphino)‐ferrocene) and diphenylphosphoric acid (DPPA) that was previously used in the thiocarbonylation led to 81 % of 2 a (Table , entry 1). Whereas, the original alkoxycarbonylation conditions ( L2 , (dtbpx; bis(di‐ tert ‐butylphosphinomethyl)benzene)/BNPA (1,1′‐bi‐2‐naphthol phosphoric acid)) generated only 73 % yield (entry 2).…”
Section: Methodsmentioning
confidence: 63%
“…[4] The control of regioselectivity is one of the challenges of this transformation. [6] Better resultsw ere achieved by Manabe et al,w ho developed ac yclization of 2-vinyl aryl formatesu sing Ru 3 (CO) 12 under forcing reaction conditions (135 8C, 15 mol %o f[ Ru]). [5] Ag eneral methodf or the synthesis of benzofuran-2(3H)-ones (2)f rom alkenylphenols (1)p roved more difficult (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Pd(II) salts such as Pd(OAc) 2 might undergo an acid‐base reaction leading to complex with replaced acetate anions. Furthermore, acid might accelerate the methanolysis by protonation of the acyl complex D …”
Section: Cooperative Catalysismentioning
confidence: 99%
“…Coupled with our interestinmetal-catalysed carbonylation [17] and in the synthesis of indoles, [18] we were attracted to the possibility of am odification of the approacho fD onga nd Busacca [15a] to obtain 3-substitutedi ndoles that would avoid the use of substrates obtained through the Heck reaction. To this end, ah ydroformylation approach based on 2-alkynylanilines, produced throught he well-established Pd-catalysed Sonogashira coupling reaction, was envisaged (Scheme 2).…”
mentioning
confidence: 99%